2006
DOI: 10.1128/aac.00573-06
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Resistance and Differential Protein Expression of Salmonella enterica Serovar Enteritidis Biofilms Exposed to Benzalkonium Chloride

Abstract: The development of adaptive resistance of Salmonella enterica serovar Enteritidis ATCC 4931 biofilms following exposure to benzalkonium chloride (BC) either continuously (1 g ml ؊1 ) or intermittently (10 g ml ؊1 for 10 min daily) was examined. Biofilms adapted to BC over a 144-h period could survive a normally lethal BC challenge (500 g ml ؊1 for 10 min) and then regrow, as determined by increases in biofilm thickness, total biomass, and the ratio of the viable biomass to the nonviable biomass. Exposure of un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(59 citation statements)
references
References 54 publications
3
56
0
Order By: Relevance
“…Gene rfbH is required for S. Enteritidis to survive in egg albumen (23), which also plays a role in the adaptive resistance of S. Enteritidis biofilms to benzalkonium chloride (41). Mizumoto et al (46) suggested that LPS structure in S. Enteritidis may contribute to the attachment to chicken vaginal explants.…”
Section: Resultsmentioning
confidence: 99%
“…Gene rfbH is required for S. Enteritidis to survive in egg albumen (23), which also plays a role in the adaptive resistance of S. Enteritidis biofilms to benzalkonium chloride (41). Mizumoto et al (46) suggested that LPS structure in S. Enteritidis may contribute to the attachment to chicken vaginal explants.…”
Section: Resultsmentioning
confidence: 99%
“…The stress response during biofilm formation is a well-reported phenomenon in E. coli and Salmonella (88)(89)(90). The stress and ycfR induction can alter the cell surface hydrophobic properties, resulting in inhibition of biofilm maturation/stability.…”
Section: Discussionmentioning
confidence: 99%
“…Chlorine consumption of such biofilm was increased, suggesting that adaptation to chlorine stress induces a hyper-production of exopolymeric substances that can protect the viable cells. Salmonella biofilm cells were also reported to display a greater adaptation than their planktonic counterparts to BCK after continuous exposure to 1 µg/mL of this disinfectant (Mangalappalli-Illathu & Korber, 2006). Specific proteins involved in energy metabolism, protein biosynthesis, nutrient binding, cold shock and detoxification were up-regulated.…”
Section: Implication Of Biofilms In the Tolerance Response Of Salmonementioning
confidence: 99%
“…Specific proteins involved in energy metabolism, protein biosynthesis, nutrient binding, cold shock and detoxification were up-regulated. Conversely, proteins involved in proteolysis, cell envelope formation, universal stress, heat shock response (Dnak) and broad regulatory functions (Hns) were down-regulated following adaptation (Mangalappalli-Illathu & Korber, 2006).…”
Section: Implication Of Biofilms In the Tolerance Response Of Salmonementioning
confidence: 99%